The concept of business cooperation in the formation of logistics distribution channels (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The article is devoted to the formation of a theoretical concept about the loyalty of consumers in the distribution channels of finished products as some complex economic phenomenon.The article addresses the problem of distribution channels and their effective formation which is one of the utmost importance at present time. The results showed that distribution channels are an important link in the value chain, which contribute to achieving a balance of interests of functionally related businesses that ensure the delivery of goods from producer to consumer. It is determined that the recent changes in the activities of wholesale and retail intermediaries are associated with changes in purchasing behavior, the development of network retail, the emergence of new forms and methods of selling goods, the active use of information technology and online interaction.Goal. Development of conceptual provisions for business cooperation in marketing distribution channels.Results. It is substantiated that the traditional market space, dominated by the manufacturer, is evolving and is now taking the form of what is called a market space focused on distribution. It is proved that within this space there is a shift of emphasis from competitive relations between participants of distribution channels to relations of cooperation and partnership. This requires the development of new mechanisms of interaction in such distribution channels, taking into account the economic interests of their participants and ensuring consistency of action based on the concept of business cooperation.It is noted in the article that the need to expand the boundaries of interaction arises due to the need to increase the efficiency of enterprises through the possibility of using the skills, resources and assets of business partners. It is proved that cooperation in modern conditions becomes the basis for ideas generation, innovations development, and a source of sustainable competitive advantages that contribute to the formation of a unique strategic asset – a partnership network based on a long-term mutually beneficial relationships of business partners in the chain of created value. At the same time, the refusal to cooperate leads to differences in the interests, goals and functions of participants in marketing distribution channels, which entails conflicts and increases costs in the process of delivery of goods from producer to final consumer.